Diego Melo Carrasco, Miguel Ángel Manzano Rodríguez (coords.),Al-Andalus y el Magreb. Miradas trasatlánticas. Gijón: Ediciones Trea, 2019. ISBN- 978-84-17767-25-9. - Bueno Sánchez, Marisa (De Medio Aevo, 2020)
Reseña del libro de Diego Melo Carrasco, Miguel Ángel Manzano Rodríguez (coords.),Al-Andalus y el Magreb. Miradas trasatlánticas. Gijón: Ediciones Trea, 2019. ISBN- 978-84-17767-25-9.